Exploring the Impact of Work-Life Balance, Job Satisfaction, and Training on Employee Performance: A Literature Review - Ahmad Dafa Bahits Rizqulloh; Wicaksono Andy Kuncoro (Arthatama: Journal of Business Management and Accounting, 2022)
This study explores the interplay between job satisfaction, Work-Life Balance (WLB), and employee performance, highlighting the critical role of organizational training and support. Job satisfaction has long been recognized as a key driver of employee performance, fostering motivation and engagement. The research suggests that organizations providing continuous learning opportunities can enhance job satisfaction, which in turn positively impacts performance. Moreover, work-life balance has a significant influence on both job satisfaction and employee performance, particularly when organizations implement supportive policies such as flexible working hours. However, the effects of WLB can vary across employee types, with temporary employees sometimes showing less concern for WLB in favor of job stability. Training also plays a pivotal role in improving employee performance by equipping workers with relevant skills and reducing stress. In high-pressure environments, targeted and relevant training can have a more substantial impact on job satisfaction and performance than merely promoting work-life balance. This study emphasizes that while WLB and job satisfaction are interconnected, organizational factors such as leadership, training, and commitment are essential in maximizing employee performance. Ultimately, a balanced approach that integrates WLB with effective training and organizational support can enhance overall workforce productivity.